Visualization of lithiated/delithiated particle distribution in Li4Ti5O12 electrode by ultralow-voltage scanning electron microscopy imaging - Mitsunori Kitta (Electrochemistry Communications)
Characterization of the spatial distribution of lithiated/delithiated particles in Li-ion battery electrodes would facilitate an understanding of the reactions taking place. Here, ultralow-voltage (<1 kV) accelerated scanning electron microscopy (ULV-SEM) was used to visualize the distribution of lithiated/delithiated particles in the Li4Ti5O12 electrode. A conductive additive-free electrode was prepared using commercially available Li4Ti5O12 powder and partially lithiated using an electrochemical cell. The secondary electron (SE) image of the partially lithiated electrode acquired at an acceleration volage of 500 V shows a clear distribution of the lithiated/delithiated secondary particles. The contrast of the high-angle backscattered electron (HA-BSE) image of the corresponding voltage is different from that of the SE mode, providing heterogeneous physical information on the secondary particles in the electrode, such as inhomogeneous surface electronic conductive pathway of each particle. With its facile and high-throughput screening, ULV-SEM imaging is a promising method for characterizing LIB electrodes and clarifying the reactions occurring.